Ethnobotanical study of medicinal flora used by muslim traditional healers in Baloi, Lanao Del Norte - Gonzales, Doreen Khrystel; Madale, Vanjoreeh; Macaorog, Aslia; Casidar, Jamaliah; Ampaso, Soraima; Amparado, Olive; Salic-Hairulla, Monera (Ethnobotany Research and Applications, 2026)
Background: Medicinal plants remain a vital component of primary healthcare among many rural and culturally distinct communities. In Baloi, Lanao del Norte, Muslim Maranao traditional healers continue to rely on indigenous plant-based remedies for disease treatment. However, this knowledge is largely undocumented and at risk of being lost. This study aimed to systematically document and quantitatively analyze the ethnomedicinal flora used in the community to support knowledge preservation and future pharmacological exploration. Methods: A descriptive quantitative ethnobotanical approach was employed using purposive sampling of 25 key informants recognized as traditional healers. Data were collected through validated survey questionnaires, interviews conducted in the Maranao dialect, and guided field walks for plant identification. Quantitative indices, including Use Value (UV) and Informant Consensus Factor (FIC), were computed, and reported ailments were categorized using the ICD-10 classification system. Results: Results documented 28 medicinal plant species belonging to 18 botanical families, with Asteraceae as the most represented. Several species such as Annona muricata, Blumea balsamifera, Curcuma longa, and Cymbopogon citratus exhibited moderate to high UVs, indicating strong cultural importance. High to complete FIC values (0.89–1.00) were observed for common ailments including fever, diabetes, hypertension, gastrointestinal disorders, and kidney-related conditions, reflecting strong consensus among informants. Conclusions: These findings demonstrate a well-established and shared ethnomedicinal knowledge system within the community. It is recommended that conservation initiatives, community-based knowledge transmission programs, and pharmacological validation studies be undertaken to safeguard and further explore these culturally significant medicinal plants. Keywords: Ethnomedicinal plants, Maranao ethnomedicine, Muslim Ethnomedicine, Traditional healers